Unsteady stagnation point flow and heat transfer over a stretching/shrinking sheet with prescribed surface heat flux. - Nik Long, Nik Mohd Asri; Bachok @ Lati, Norfifah; Md. Arifin, Norihan; Ishak, Anuar; Suali, Melini (Asian Network for Scientific Information, 2011)
An analysis is carried out to study the unsteady two dimensio nal stagnation point flow and heat transfer over a stretching/shrinking she et with prescribed surface heat flux. The governing partial differential equations are conve rted into nonlinear ordinary dif- ferential equations using similarity variables, and solve d numerically.